2005
DOI: 10.1001/jama.294.9.1088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Work Hour Reduction on Residents’ Lives

Abstract: Past interventions suggest that residents' quality of life may improve with work hour limitations, but interpretation of the outcomes of these studies is hampered by suboptimal study design and the use of nonvalidated instruments. The long-term impact of reducing resident work hours on education remains unknown. Current and future interventions should be evaluated with more rigorous methods and should investigate links between residents' quality of life and quality of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
204
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(215 citation statements)
references
References 69 publications
3
204
1
6
Order By: Relevance
“…These alterations run the risk of decreasing clinical and procedural experience while potentially improving professional communication 3. There have been arguments for and against these changes, some believing that the number of procedures or experiences would increase and some arguing that they would decrease 31. Instituting mentoring programs, dedicated research, and/or dedicated teaching times have been found to improve resident satisfaction 3, 32.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations run the risk of decreasing clinical and procedural experience while potentially improving professional communication 3. There have been arguments for and against these changes, some believing that the number of procedures or experiences would increase and some arguing that they would decrease 31. Instituting mentoring programs, dedicated research, and/or dedicated teaching times have been found to improve resident satisfaction 3, 32.…”
Section: Discussionmentioning
confidence: 99%
“…9 We focused on burnout in this review, but other studies have corroborated the improvement in well-being by documenting more residents having babies in the post-2003 time period, 93 greater ability to attend family events, 38 and less perceived stress. 94 However, other aspects of well-being such as rates of depression do not seem to have changed between the pre-2003 period and the post-2003 period.…”
Section: Discussionmentioning
confidence: 99%
“…This allows conclusions to be drawn that were not possible when the last comprehensive reviews on this subject were published. 8,9 Limitations notwithstanding, this review provides a comprehensive synthesis of the evidence base for the 2003 duty hour reforms in the US. The balance of evidence suggests that burnout among residents has decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] Training programs began to institute necessary changes but in doing so, created greater patient discontinuity and increased handoffs between residents, elevating the potential for adverse patient outcomes. 12 Recent largescale studies indicate that inpatient care is the same or improved since adoption of the duty hour restrictions, [13][14][15][16] but controversy continues, with several editorials debating the issue.…”
Section: Resident Duty Hour Restrictionsmentioning
confidence: 99%